From Labour Market Institutions to an Alternative Model of Labour Markets. Issue 1 (2nd January 2017) - Fleetwood, Steve
Abstract : This post-disciplinary article goes beyond orthodox labour economics and combines insights from the 'socio-economics of labour markets' (SELM), and critical realism (CR), to develop a SELM CR perspective, which is then used to create an alternative conception of labour market institutions and an alternative model of labour markets, i.e. the SELM CR model.